Pamir Territory - Shafi'i, Malek (Afghanistan : CACA-Kabul)
A group of filmmakers travel to Pamir, the farthest region of Afghanistan which borders Pakistan, Tajikistan and China. Wakhan, part of Badakshan Province, is a mountainous and rugged part of the Pamir and Karakoram regions of Afghanistan. Eshkashem is a town in Badakhshan Province. On the pretext of elections, the filmmakers manage to cross Faiz Abad, head to Eshkashem and see Wakhan. The result is "Pamir Territory" which is a film about the people of Pamir, their lives and hardships, their social and economic situation in relation to the political events in Afghanistan - the elections.
Verzio Film Festival Submission
Keywords: Afghanistan